‘From Data to Decisions- Harnessing Artificial Intelligence for Effective Business and Software Management’ - Siddhesh Nasnodkar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the realm of contemporary corporate and software management, the pivotal role of Artificial Intelligence (AI) in renovating raw data into informed decisions cannot be excessive. This research delves into the intricate process of navigating from data acquisition to strategic decision-making, elucidating the profound impact of AI technologies on enhancing efficacy in both business and software realms. By leveraging advanced algorithms and machine learning capabilities, organizations can harness the power of AI to sift through vast datasets, derive meaningful insights, and facilitate more nuanced decision-making processes. The study examines how AI acts as a catalytic force in distilling complex information, offering decision-makers a comprehensive and timely understanding of intricate business dynamics. Furthermore, it investigates the symbiotic relationship between effective business management and software optimization, exploring how AI-driven insights can streamline software development processes and bolster overall organizational efficiency. In this ever-evolving landscape, understanding and maximizing the potential of AI for data-driven decision-making emerges as a crucial imperative for businesses and software enterprises alike, positioning them to thrive in the dynamic digital era.